WoT model for authenticity contents in virtual learning platforms - Gaona-García, Paulo Alonso; Soto-Carrión, Jesús (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
The following research proposal seeks to bring a model of security software on virtual learning platforms LCMS under all SCORM specifications to ensure the authenticity of content created under concepts of digital signature and identification of protocols and mechanisms to ensure such activities.
Keywords: security; authenticity mechanisms; virtual learning platforms; LCMS; SCORM; digital signatures; certificates of authentication; IJIMAI